2016
DOI: 10.5152/balkanmedj.2015.15159
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Algorithm for the Detection of Clostridium difficile-Associated Diarrhea

Abstract: Background: Clostridium difficile is a common cause of hospital-acquired diarrhea, which is usually associated with previous antibiotic use. The clinical manifestations of C. difficile infection (CDI) may range from mild diarrhea to fulminant colitis. Clostridium difficile should be considered in diarrhea cases with a history of antibiotic use within the last 8 weeks (community-associated CDI) or with a hospital stay of at least 3 days, regardless of the duration of antibiotic use (hospital-acquired CDI). Aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
1
24
0
1
Order By: Relevance
“…All researchers agree that high sensitivity values, even more negative predictive rule values, low cost, short time and simple performance make GDH tests a powerful reagent especially when combined with another toxin test within two or three steps of the CDI diagnosis algorithm (5,6,8,11,13). The high values of the characteristic of the tests used to detect GDH in our study, despite a small sample, are confirmed by previous attitudes.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…All researchers agree that high sensitivity values, even more negative predictive rule values, low cost, short time and simple performance make GDH tests a powerful reagent especially when combined with another toxin test within two or three steps of the CDI diagnosis algorithm (5,6,8,11,13). The high values of the characteristic of the tests used to detect GDH in our study, despite a small sample, are confirmed by previous attitudes.…”
Section: Discussionsupporting
confidence: 88%
“…Tests that detected both toxins (individually or both at the same time) were more reliable. In general, the results obtained indicate that the detection of both toxins by one test takes precedence over tests that only detect toxin A (performance values, above all specificity, of the tests were over 90% (eg C. diff Toxin A + B, Diagnostic Automation Inc., Calabasas, CA, USA; Cytoclone A/B Meridian Diagnostic, Cincinnati, Ohio; Remel prospect C. difficile toxin AB, Microplate, Lenexa, KS) (6,8,9).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations